PENATALAKSANAAN FISIOTERAPI PADA KONDISI “TOTAL HIP REPLACEMENT” DENGAN MODAL INFRA MERAH DAN TERAPI LATIHAN DI RS ORTHOPEDI DR. R. SOEHARSO SURAKARTA - Anna Maulidia Khairunissa; Eko Budi Prasetyo (LPPM Universitas Pekalongan, 2020)
Total Hip Replacement is the replacement of both sufaces of the hip joint that are experiencing degeneration. This means that the joint are replaced (conventional) or trimmed and covered with metal caps (resurfacing). The post operative problems of Total Hip Replacement are pain, spasm, differences leg length, decreased joint motion, decreased muscle strength, and decreased functional ability activities. Physiotherapy examination of pain with Verbal Descriptive Scale, spasm with palpation, leg length differences with midline, scope of joint motion with goniometer, muscle strength with a Manual Muscle Testing scale, and functional ability activity with the Oxford Hip Score index. In this case the technology chosen was Infra Red and Exercise Therapy.The purpose of this study was to determine the effect of physiotherapy management on post operative conditions Total Hip Replacement with Infra Red modality and Exercise Therapy. This research was conducted at RS Orthopedi Dr. R. Soeharso Surakarta with a descriptive analytic research design. Subjects were patients with post operative Total Hip Replacement with Infra Red and Exercise Therapy. Research instruments in the form of Visual Descriptive Scale (VDS), palpation, midline, goniometer, Manual Muscle Testing (MMT), and Oxford Hip Score Scale.The results of the study were 2 times the following therapy : (1) there was a decrease in pain (2) there was a decrease in muscle spasm (3) there was no change in leg length (4) there was no increase in joint range of motion (5) there was no increase in muscle strength (6) there is no increase in the ability of functional activities. The conclusion of this study is that physiotherapy intervention with Infra Red modality and Exercise Therapy can reduce the problems that arise in the postoperative condition of Total Hip Replacement.